The History of Women’s Mosques in Chinese Islam: A Mosque of Their Own by Maria Jaschok and Shui Jingjun (London: Routledge & Curzon Press, 2000. 361 pages.) (American Journal of Islam and Society, 2006)
This remarkable collaboration of primarily Maria Jaschok and Shui Jingjun(with contributions from nine other mostly Muslim Chinese women who areduly acknowledged), contains a wealth of information on a subject that most scholars of Muslim communities have never considered or perhaps evenimagined: the existence of bona fide women’s mosques in China. Throughpainstaking historical, archival, interview, and field research, the authors layout a convincing argument that such mosques have existed in China and continueto experience a “rapid increase” (p. 15), at least since the late Mingdynasty (sixteenth to seventeenth centuries), proliferating in northern China’scentral plains region (mainly Henan, Hebei, Shandong, and Anhui) during theQing emperor Jiaqing’s reign (1796-1820) (pp. 67-69).This work sheds light on “how women [in China] engendered and sustainedfaith, aspiration and loyalties under often challenging conditions” (p.5) – which is putting it mildly. Strenuously caught between Confucian,Islamic, and patrimonial requirements, they developed an institution of learningand cultural transmission perhaps unique to the Muslim world. While theauthors never fully address why “women’s mosques” and madrassahs developedso fully in China (and almost nowhere else), they do richly demonstratethe extraordinarily important role these religious and educational centershave played in preserving and promoting Islamic understanding amongChina’s Muslims, known as the Hui national minority (with a year 2000 populationof approximately 9.8 million, out of a total 20.3 million Muslims inChina, according to the especially accurate PRC state census).While the authors claim these women’s “prayer halls” (the Chinese termis ambiguous) and the women who lead them are fully-fledged ahongs orimams (again, the Chinese term, like the Arabic and Persian equivalents, isnot clear about the teacher’s actual status), the issue here is whether they haveany authority over men. Since they clearly do not, ahong should be taken inits more general sense of “one possessing advanced Islamic knowledge” ortraining, and does not imply institutionalized authority beyond the sphere ofwomen (and children, which in most instances includes boys). Nevertheless,it is significant that they have such organized authority, training, and separateprayer halls or mosques among themselves ...